Consumer profile analysis for different types of meat in Spain. (July 2017) - Escriba-Perez, Carmen; Baviera-Puig, Amparo; Buitrago-Vera, Juan; Montero-Vicente, Luis
Abstract: It is important to analyse the consumer profile of each type of meat to better adapt the marketing mix to each one. To this end, we examined the average consumption frequency of different types of meat based on two methodologies: consumer segmentation using the food-related lifestyle (FRL) framework, giving rise to 4 segments, and analysis of socio-demographic profiles. The variables used were: sex, age, educational level, social class, number of people in the household, presence of children younger than 18 in the home, geographical area and habitual residence. Beef was the only meat type significant in both analyses. Turkey meat only appeared as significant in the FRL analysis. The other meats (chicken, pork, rabbit and lamb) were only significant in the sociodemographic variables analysis. From the outcomes we may conclude that there is no single consumer profile, which rather depends on the type of meat. Highlights: The variable studied is the average consumption frequency of different meat types. Beef and turkey meats are associated to the consumers' food-related lifestyle. Chicken, pork, rabbit and lamb meats depend only on sociodemographic variables. As a result, a different consumer profile is obtained for every type of meat. Therefore, the marketing mix should be adapted to each type of meat and consumer.